Forgiving and Forgetting: A Post-Holocaust Dialogue on the Possibility of Healing - Thomasma, David C. (Cambridge quarterly of healthcare ethics, 2000)
At the end of this century there are so many occasions, so many residues of the most violent of times, that challenge the very idea of forgiveness—residues personal, political, social, and cultural. The harms are vast and yet close to home: alcoholism takes its toll on relationships, divorce undermines love, parental harshness and abuse create generations of problems for offspring, addictions of every sort turn humans into caged spirits. Additional and even greater challenges include infidelity, breaking public promises, political power plays, torture, genocidal slaughtering of races and tribes, civil and cultural wars, ancient enmities—Northern Ireland, Bosnia, the Tutsis and Hutus, the Shiite and Suni Moslems, the settlers and African immigrants in South Africa, indigenous populations against the dominant culture. The open violence and rapaciousness of human enmity can be viewed now in the displacement of masses of people in Kosovo. Said the U.N. High Commissioner for Refugees, Sadako Ogata, about the Kosovo crisis: “It is frightening … that this century, as in its darkest hours, should end with the mass deportation of innocent people.”